Simulation analysis for assembly line workstation layout: case study - Intan Bazliah, Mohd; Abdullah, Ibrahim (UTeM, 2019)
The paper explores the cost saving projects that have been implemented in an electrical product assembly line, so called subwoofer speaker. Observation has been conducted on 26 workstations which are involved in an assembly line. Group discussion, real time study and simulation analysis have been performed to reduce operational cost. The result shows that the proposed layout was improved at least 22.68% space utilisation in the production area but only able to improve at least 0.56 percent of production rate. The simulation result gave the production personnel to decide the best improvement workstation layout and enhance the participation of employee in cost saving activities while improve production capacity.